AKIBAT HUKUM PERJANJIAN KERJA SECARA LISAN MENURUT PERSPEKTIF HUKUM KETENAGAKERJAAN - Mulia Syahputra Nasution; Suhaidi Suhaidi; Marzuki Marzuki (Jurnal Ilmiah METADATA, 2021)
An employment agreement is an agreement made between an employer and an employer, which is the starting point for an employment relationship. Manpower Act, to make a written employment agreement. Verbal employment agreements are also considered valid by law. It is important to have a written work agreement as a binding and as evidence. In practice, it is not uncommon for work relationships to be carried out without being based on a written work agreement so that it will cause legal problems, especially regarding workers' rights. The formulation of the problem in this thesis is how to arrange a work agreement in the perspective of labor law, the status of workers who carry out a work relationship with an oral work agreement, the legal consequences of working relations based on an oral work agreement in the perspective of labor law. The research method used is descriptive analysis which leads to normative juridical legal research, namely research carried out by referring to legal norms, namely examining library materials or secondary materials. Secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials. The results show that the position of a work agreement orally based on the perspective of labor law has a strong position, which is valid as long as it does not contradict the legal conditions of the work agreement as regulated in Article 52 of the Manpower Act, legal consequences of working relations based on the work agreement. Orally According to the provisions of the Employment Law, namely an oral work agreement, has several legal consequences, if the work relationship is in the form of a specified time work agreement (PKWT) which is made orally, then the status changes to an indefinite work agreement (PKWTT). Legal Protection for Workers in a Work Relationship Based on an Oral Agreement According to the Manpower Law Provisions, namely a verbal employment agreement has not been able to provide full legal protection to the parties, especially workers.